ضغوط العمل التنظيمية وعلاقتها بالوظائف الإدارية لدى مديري مدارس محافظة معان - وصوص، ديمة محمد محمود سليمان; الرواد، ذيب محمد Alrowwad, Dheeb Mohammed (جامعة الحسين بن طلال - عمادة البحث العلمي والدراسات العليا, 2016)
The goal of this research is to identify the level of the regulatory pressures of work and the level of the performance of the administrative positions for the school directors in Ma'an governorate, and to identify whether there is a relationship, that has a statistical significance at the significance level (a=0.05), between the means of estimates of the study samples at the level of the regulatory pressures of work and if there were differences that have a statistical significance for the following variables; gender, qualification, administrative experiences, and numbers of training sessions. In order to achieve this, the analytical correlative approach was used, to commensurate with the nature of this study, through the collection and analysis of this research problem by using the questionnaire that is devided into two parts; the regulatory pressures of work and the performance of the administrative positions. This study included all the directors of schools in Ma'an governorate who reach the number of (189) principals, and a random selection was made, where the study samples consisted of (112) principals. The result was that the means of the estimates of the study samples on the area of the regulatory pressures of work was large, and on the area of performance of the administrative positions was high, and there is a strong positive proportional relationship that has a statistical significance in between the estimates of the study samples on the level of regulatory pressures of work with the directors of schools in Ma'an governorate and their estimates on the level of the performance of the administrative positions.
هدف هذا البحث التعرف على مستوى ضغوط العمل التنظيمية ومستوى أداء الوظائف الإدارية لدى مديري المدارس في محافظة معان، والتعرف إذا ما كان هناك علاقة ذات دلالة إحصائية عند مستوى الدلالة (α = 0.05) بين المتوسطات الحسابية لتقديرات أفراد العينة على مستوى ضغوط العمل التنظيمية، وإذا ما كان هناك فروق ذات دلالة إحصائية لمتغيرات: (الجنس، والمؤهل العلمي، والخبرة الإدارية، وعدد الدورات التدريبية). ولتحقيق ذلك استخدم المنهج الارتباطي الذي يتناسب وطبيعة هذه الدراسة، وذلك من خلال جمع وتحليل بيانات هذه المشكلة باستخدام الاستبانة التي تنقسم إلى محورين، هما: محور ضغوط العمل التنظيمية، ومحور أداء الوظائف الإدارية. وشمل مجتمع الدراسة جميع مديري مدارس محافظة معان والبالغ عددهم (189) مديرا ومديرة، وتم اختيار عينة طبقية عشوائية من مجتمع الدراسة، حيث تكونت العينة من (112) مديرا ومديرة. توصلت النتائج إلى أن المتوسط الحسابي لتقديرات أفراد العينة على مجال ضغوط العمل التنظيمية كان بدرجة كبيرة. وأن المتوسط الحسابي لتقديرات أفراد عينة الدراسة على مجالات مستوى أداء الوظائف الإدارية كان مرتفعا، وأن هناك علاقات إيجابية طردية قوية ذات دلالة إحصائية بين متوسطات تقديرات أفراد العينة على مستوى ضغوط العمل التنظيمية لدى مديري مدارس محافظة معان وتقديراتهم على مستوى أداء الوظائف الإدارية.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- طرق التدريس -- المؤسسات التعليمية -- ضغوط العمل -- الوظائف الإدارية -- مدارس محافظة معان -- مدراء المدارس -- الأردن -- المجتمع الأردني -- مستخلصات الأبحاث -- الترجمة -- اللغات الأجنبية